2022
DOI: 10.3390/math10214001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of COVID-19 Data Using an ARIMA-LSTM Hybrid Forecast Model

Abstract: The purpose of this study is to study the spread of COVID-19, establish a predictive model, and provide guidance for its prevention and control. Considering the high complexity of epidemic data, we adopted an ARIMA-LSTM combined model to describe and predict future transmission. A new method of the ARIMA-LSTM model paralleling by weight of regression coefficient was proposed. Then, we used the ARIMA-LSTM model paralleling by weight of regression coefficient, ARIMA model, and ARIMA-LSTM series model to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The first method is to combine the time series model with the machine learning model. For example, Jin et al [24] used the hybrid forecasting model of ARIMA-LSTM to predict the changing trend of COVID-19 in China in the upcoming 50-60 days (11 October 2022 to 9 December 2022). Su [25] used a combined ARIMA-SVR model to perform forecasting analysis of financial markets.…”
Section: Predictive Model Based On a Combination Of Different Methodsmentioning
confidence: 99%
“…The first method is to combine the time series model with the machine learning model. For example, Jin et al [24] used the hybrid forecasting model of ARIMA-LSTM to predict the changing trend of COVID-19 in China in the upcoming 50-60 days (11 October 2022 to 9 December 2022). Su [25] used a combined ARIMA-SVR model to perform forecasting analysis of financial markets.…”
Section: Predictive Model Based On a Combination Of Different Methodsmentioning
confidence: 99%
“…The output of prevention involves considering sentence analysis and decision sentences. In the below table 3 represent prevention by giving suggestion as per rule based outcomes data [33]. 1) Sentence Analysis: Sentence Analysis represents the physical data of the person as glucose level of person fuzzy numbers like Glucose(low, medium or high).…”
Section: Prevention Experimental Detailsmentioning
confidence: 99%
“…To enhance the dependability of their predictions, Kumar et al [22] proposed the use of a spline function to segment the non-linear epidemic time series into different growth stages and predict it at different stages of spread of the infection with a linear modeling approach, which reduces the difficulty of prediction. Some researchers synergistically amalgamated the strengths of several models to devise hybrid models [23][24][25][26][27]. The results found that combining convolutional neural networks with temporal recurrent neural networks (e.g., CNN-LSTM, CNN-GRU) to capture the local spatial correlation and long-term dependence of historical daily new cases has significantly better predictive performance than a single model.…”
Section: Literature Reviewmentioning
confidence: 99%